(untitled) (Latakia University Journal -Biological Sciences Series, 2023)
The aim of resarch was to study the effect of foliarspray with different concentrations of gibberellin acid (0, 50, 100, 150 ppm) and two planting distances (15 ×15), (30×30) cm and both of them together in vegetative growth and flowering of the plant. The results showed the positive effect of the growth regulator on the development of the vegetative variety (length of plant, number of leaves, leaf area, freshweight, dryeeight, percentage of dry matter and the amount of total chlorophyll), as well as the formation and evolution of flowering (early flowering, number of flower stem, total of flowers, number of flower on flower stem and floral diameter) especially when use the highest concentration of growth regulator (150 ppm) and plant at (30×30) cm planting distances. The results showed the remarkable effect of highest concentration of gibberellins acid and highest planting distances on commercial pick flower stem.